Rangamandapa of the Ghateshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The rangamandapa (an open type of pillared hall used for ceremonial rituals) consists of a large number of heavy, ornately carved pillars that support the ceiling. The mandapa (pillared hall) has small projections and kakshasana (seat backs) on all four sides. The east and west sides of the mandapa are open, allowing entry. A pediment at the base of the pyramidal roof is filled with the figures of gods and goddesses.